Absceso cerebral secundario a otitis media supurativa crónica en paciente de 20 años de edad - Ganchozo Celi, Edinson Fabian (2018)
INTRODUCTION: Otitis media (OM) is a disease that most often children suffer. (1) is presented as an infection in the middle ear, being its viral or bacterial etiology. The most common causal germs are streptococcus pneumoniae, Haemophilus influenzae, Moraxella catarrhalis, and Streptococcus, Staphylococcus aureus, e. coli, Pseudomonas aeruginosa less usual; viral agents such as respiratory syncytial virus, parainfluenza and influenza, the major complications are extracranial and intracranial; between the intracranial cerebral abscess is located. (2) The AC is a rare disease, which is caused by an infectious process located in the cerebral parenchyma. (3) they occur as the outcome of infection of neighbouring anatomic structures. (4) Brain abscesses, arising as a complication of otitis media, are formed from infections, being the most frequent agents Streptococcus and anaerobic bacteria. (5) In developing countries there is a big impact of the complications of the otitis media, who reveals 51,000 deaths annually in children under five, attributable to the pathology by complicating intracranial infections. (1) The purpose of the analysis of the present case, is to describe information about otitis media, which can lead to the formation of brain abscess as a complication of the same, and in turn socialize obtained with the academic community and the public in General. It has conducted research based on scientific papers such as journals and bibliographic material concerning the subject, which has contributed to the obtaining of truthful knowledge about this problem. Giving way to the development of a plan of nursing care that allows individually address the needs of the patient with brain abscess secondary to otitis suppurative media, considering the special care, that deserves this kind of infections due to its limited presence in adults. OBJECTIVE: To analyze a real case of a patient of 20 years of age with a diagnosis of brain abscess secondary to otitis media Chronic suppurative, through documentary review of the clinical history and bibliographic sources, allowing the development of specific nursing care in this pathology. METHODOLOGY: Qualitative type research, applied clinical and descriptive method, based on the unit of analysis, a case of brain abscess secondary to Chronic suppurative otitis media, attended in the Ecuadorian Institute of Social Security (IESS), the city of Machala in the period November-December 2017. RESULTS: The clinical manifestations of brain abscess secondary to Chronic suppurative otitis media, of a 20-year-old patient are episodes of headache, dizziness and drainage in right ear, making it impossible him to open the right eye, vomiting, increase thermal. He was nursing care specific, which provide a useful tool to provide response to the vital needs of the patient. CONCLUSIONS: We conclude that otitis media is common in pediatric patients, but it has become clear that can occur in adult patients, but to a lesser extent. The continuity of the clinical manifestations of otitis media is transcendental For intracranial or extracranial complications. Patients suffering from otitis media have deficits of hearing as a sequel. Specific nursing care for brain abscess as a complication of otitis media are not evident.